Astrophysics of Galaxy Clusters - Cavaliere, A. (IOS Press, 2014)
This book presents a collection of contributions from the 'International School of Physics “Enrico Fermi”, held in Varenna, Italy in July 2008. This is the second school devoted to the astrophysics of galaxy clusters, and comes four years after the first; 'Background Microwave Radiation and Intra-cluster Cosmology'. The motivation for this second school was provided by the significant expansion in research into these, the largest gravitationally bound systems, and by the great interest in multifaceted observational, theoretical and numerical simulations of clusters. Topics were dealt with in a series of ten pedagogical reviews, and the program also included eight seminar talks. Written versions of most of these reviews and talks are published in this volume. The papers included here provide a useful updated account of key aspects of a wide range of topics in cluster research. This volume is dedicated to the memory of Professor Francesco Melchiorri, a leader in experimental Cosmic Microwave Background research and a mentor to many.